The Role of Extrinsic and Intrinsic Motivation in Enhancing Employee Performance under Entrepreneurial Leadership of Public Worker - Ibrahim Zaky; Andre Dwijanto Witjaksono; Anang Kistyanto (Image : Jurnal Riset Manajemen, 2025)
The new paradigm in public services during the current era of regional autonomy provides extensive opportunities for governments to innovate in delivering services to the community. Gunung Anyar Regency, as part of the Surabaya City Government, aims to enhance the quality of public services through digital-based bureaucratic transformation. This research examines the effect of Entrepreneurial Leadership (EL) on employee performance with extrinsic motivation and intrinsic motivation as mediating variables. The results indicate that Entrepreneurial Leadership significantly affects both Extrinsic Motivation and Intrinsic Motivation in Gunung Anyar District, Surabaya City, and has a significant direct impact on employee performance. However, extrinsic motivation does not significantly influence employee performance, whereas intrinsic motivation does. Extrinsic motivation does not significantly mediate the relationship between Entrepreneurial Leadership and employee performance, whereas intrinsic motivation significantly mediates this relationship. These findings suggest that to improve employee performance, efforts should focus on enhancing intrinsic motivation alongside strengthening entrepreneurial leadership. The leadership development strategy in Gunung Anyar District must prioritize increasing employee intrinsic motivation to achieve optimal performance.